2015
DOI: 10.1007/s12032-015-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of focal adhesion kinase on the motility, proliferation and apoptosis of Caco2 and SMMC-7721 cells

Abstract: Focal adhesion kinase (FAK) plays important roles in cancer development. However, the significance of FAK expression in colorectal carcinoma and hepatocellular carcinoma has not been clarified. This study aims to explore the roles FAK played in the progression of colorectal carcinoma and hepatocellular carcinoma. RNAi method was used to inhibit the expression of FAK in Caco2 and SMMC-7721 cells. Reverse transcriptase polymerase chain reaction analysis and Western blot analysis were used to examine mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Focal adhesion kinase is typically located at structures known as focal adhesions from where it transduces signals into cells that control multiple cancer-related events, including migration, invasion, angiogenesis, protection of cells from suspension-induced cell death and proliferation in three-dimensional matrices [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinase is typically located at structures known as focal adhesions from where it transduces signals into cells that control multiple cancer-related events, including migration, invasion, angiogenesis, protection of cells from suspension-induced cell death and proliferation in three-dimensional matrices [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Desiring to test this hypothesis, we opted to approach the crux by enhancing the expression levels of our proteins of interest, since earlier studies had shown that FAK1 depletion is associated with apoptosis 37 , 38 and that a reduction in Simiate triggers cell death within only hours 12 . Given that dendritic retraction is one of the very first reaction in apoptosis, such a condition would subvert any analysis on dendritogenesis.…”
Section: Resultsmentioning
confidence: 99%